Genome-wide identification and expression profile analysis of the NAC transcription factor family during abiotic and biotic stress in woodland strawberry. - He Zhang; Hao Kang; Chulian Su; Yanxiang Qi; Xiaomei Liu; Jinji Pu (PLoS ONE)
The NAC transcription factors involved plant development and response to various stress stimuli. However, little information is available concerning the NAC family in the woodland strawberry. Herein, 37 NAC genes were identified from the woodland strawberry genome and were classified into 13 groups based on phylogenetic analysis. And further analyses of gene structure and conserved motifs showed closer relationship of them in every subgroup. Quantitative real-time PCR evaluation different tissues revealed distinct spatial expression profiles of the FvNAC genes. The comprehensive expression of FvNAC genes revealed under abiotic stress (cold, heat, drought, salt), signal molecule treatments (H2O2, ABA, melatonin, rapamycin), biotic stress (Colletotrichum gloeosporioides and Ralstonia solanacearum). Expression profiles derived from quantitative real-time PCR suggested that 5 FvNAC genes responded dramatically to the various abiotic and biotic stresses, indicating their contribution to abiotic and biotic stresses resistance in woodland strawberry. Interestingly, FvNAC genes showed greater extent responded to the cold treatment than other abiotic stress, and H2O2 exhibited a greater response than ABA, melatonin, and rapamycin. For biotic stresses, 3 FvNAC genes were up-regulated during infection with C. gloeosporioides, while 6 FvNAC genes were down-regulated during infection with R. solanacearum. In conclusion, this study identified candidate FvNAC genes to be used for the genetic improvement of abiotic and biotic stress tolerance in woodland strawberry.